2021
DOI: 10.1177/03331024211040467
|View full text |Cite
|
Sign up to set email alerts
|

Salivary CGRP can monitor the different migraine phases: CGRP (in)dependent attacks

Abstract: Background CGRP plays a key role in the transmission and modulation of nociceptive signals and is a critical component in the pathogenesis of migraine. Objective To assess saliva as a substrate to measure CGRP by comparing interictal levels in patients with episodic migraine and controls; and to evaluate CGRP’s temporal profile during migraine attacks. Methods This prospective observational pilot study included young women with episodic migraine and healthy controls. We monitored salivary CGRP-like immunoreact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 46 publications
3
49
0
4
Order By: Relevance
“…As CGRP is a powerful vasodilator, one possible explanation of our findings would be that GR has increased interictal secretion of endogenous perivascular CGRP than non-responders. Indeed, differences in salivary levels of CGRP between patients and controls were found not only during migraine attacks but also in the interictal phase ( 14 , 15 ). Interestingly, Greco et al assessed CM patients with overuse of medications and found that responders to the detoxification had significantly higher baseline levels of CGRP as compared to non-responders ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…As CGRP is a powerful vasodilator, one possible explanation of our findings would be that GR has increased interictal secretion of endogenous perivascular CGRP than non-responders. Indeed, differences in salivary levels of CGRP between patients and controls were found not only during migraine attacks but also in the interictal phase ( 14 , 15 ). Interestingly, Greco et al assessed CM patients with overuse of medications and found that responders to the detoxification had significantly higher baseline levels of CGRP as compared to non-responders ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In interictal episodic migraine (EM) patients elevated (78)(79)(80) as well as unchanged CGRP levels were found in peripheral blood compared to healthy controls (71,73,77,81).…”
Section: Interictal Cgrp In Episodic Migraine Patientsmentioning
confidence: 99%
“…Further studies would be required to assess the utility of brinogen as a biomarker to distinguish MA from stroke. A recent study has shown that CGRP salivary levels are increased in migraine patients compared to controls, especially in ictal phase [19]. Future studies could analyze the utility of this or other migraine biomarkers to rule out stroke mimics in code stroke.…”
Section: Discussionmentioning
confidence: 99%